Basis and Design of a Randomized Clinical Trial to Evaluate the Effect of Levosulpiride on Retinal Alterations in Patients With Diabetic Retinopathy and Diabetic Macular Edema - Robles-Osorio, Ma. Ludivina; García-Franco, Renata; Núñez-Amaro, Carlos D.; Mira-Lorenzo, Ximena; Ramírez-Neria, Paulina; Hernández, Wendy; López-Star, Ellery; Bertsch, Thomas; Martínez de la Escalera, Gonzalo; Triebel, Jakob; Clapp, Carmen (Frontiers in Endocrinology, 2018)
Background: Diabetic retinopathy (DR) and diabetic macular edema (DME) are potentially blinding, microvascular retinal diseases in people with diabetes mellitus. Preclinical studies support a protective role of the hormone prolactin due to its ocular incorporation and conversion to vasoinhibins, a family of prolactin fragments that inhibit ischemia-induced retinal angiogenesis and diabetes-derived retinal vasopermeability. Here, we describe the protocol of an ongoing clinical trial investigating a new therapy for DR and DME based on elevating the circulating levels of prolactin with the prokinetic, dopamine D2 receptor blocker, levosulpiride. Methods: It is a prospective, randomized, double blind, placebo-controlled trial enrolling male and female patients with type 2 diabetes having DME, non-proliferative DR (NPDR), proliferative DR (PDR) requiring vitrectomy, and DME plus standard intravitreal therapy with the antiangiogenic agent, ranibizumab. Patients are randomized to receive placebo (lactose pill, orally TID) or levosulpiride (75 mg/day orally TID) for 8 weeks (DME and NPDR), 1 week (the period before vitrectomy in PDR), or 12 weeks (DME plus ranibizumab). In all cases the study medication is taken on top of standard therapy for diabetes, blood pressure control, or other medical conditions. Primary endpoints in groups 1 and 2 (DME: placebo and levosulpiride), groups 3 and 4 (NPDR: placebo and levosulpiride), and groups 7 and 8 (DME plus ranibizumab: placebo and levosulpiride) are changes from baseline in visual acuity, retinal thickness assessed by optical coherence tomography, and retinal microvascular abnormalities evaluated by fundus biomicroscopy and fluorescein angiography. Changes in serum prolactin levels and of prolactin and vasoinhibins levels in the vitreous between groups 5 and 6 (PDR undergoing vitrectomy: placebo and levosulpiride) serve as proof of principle that prolactin enters the eye to counteract disease progression. Secondary endpoints are changes during the follow-up of health and metabolic parameters (blood pressure, glycated hemoglobin, and serum levels of glucose and creatinine). A total of 120 patients is being recruited. Discussion: This trial will provide important knowledge on the potential benefits and safety of elevating circulating and intraocular prolactin levels with levosulpiride in patients with DR and DME.